Analisis Konsep Ilmu Pengetahuan Alam Materi Getaran dan Gelombang Bunyi pada Budaya Gendang Beleq Suku Sasak - Johana Aulina Rahmatin; Barinta Nur Respasari; Leza Puastri Putri; Alfiana Chandra Dewi; Parni Hidayati; Yayuk Andayani; Aliefman Hakim; Saprizal Hadisaputra (Indonesian Journal of STEM Education, 2023)
This study aims to analyze the concept of Sound Wave Science in the culture of the Beleq Drum of the Sasak Tribe. This study uses a qualitative descriptive research method with observation, interview, and documentation study techniques. Concept analysis is used to analyze the concept of science, especially sound wave material in the Beleq Drum Culture of the Sasak Tribe which will later be developed into a culturally integrated LKPD. The results obtained are the existence of the Science Concept, especially in the sound wave material in the Beleq drum culture of the Sasak tribe, especially when playing the Beleq drum musical instrument when the drum is beaten, it will produce sound waves that will later be heard by the human sense of hearing. This can be used as a science learning medium that is quickly understood by students because the Beleq drum culture is a culture that is often found by students and a culture that must be preserved.